Siberian libraries in corporations: problems and prospects of cooperation - A. A. Stukalova (Библиосфера, 2017)
Among the libraries of research institutions of the Siberian Branch of the Russian Academy of Sciences (RI SB RAS) only 29 of 70 are members of any corporate library system. A survey of these libraries staff has identified the following issues that prevent them from working within corporate library systems: absence of electronic catalog in libraries related to lack of funding to purchase automated library information systems (ALIS), using various ALIS, different quality and uniformity missing of electronic catalogue records. The author suggests possible ways to solve these problems: transition to automated system IRBIS for libraries that work in other ALIS, joining IRBIS-Corporation, using cloud technology to embed information resources of the library.In the context of activity in library corporations, participating libraries afford their electronic catalog into the union catalogue; implement technology of corporate catalogization, interlibrary loan and electronic document delivery; solve problems of information services of users applying the corporative product. However, to resolve the whole complex of problems some libraries have to participate in several corporate systems. For effective corporate interaction libraries need a unified library corporate system combining all libraries of SB RAS’ research institutions and providing solutions to all complex problems.